Assessing the Relationship between Vocabulary Learning Strategies Use and Vocabulary Knowledge at Khairun University - Sulmi Magfirah; Nur Fajrhi (South Sulawesi Education Development (SSED), 2023)
The characteristic of vocabulary learning skills is different from any other language learning skill. It requires self-willingness and experience to achieve a higher vocabulary number or specific language proficiency level. Students with higher vocabulary knowledge seem to have tremendous advantages in comprehending language sources. At the same time, their counterparts find that vocabulary is their barrier to acquiring, understanding, and even using the target language. This study aims to examine whether or not students' vocabulary learning strategies contribute to their vocabulary knowledge. The study participants were second-year students of the English Department at Khairun University. The vocabulary strategy data were obtained from a questionnaire developed by Gu and Johnson (1996), while the vocabulary knowledge used a validated version of the Vocabulary Levels Test by Schmitt et al. (2001) and the Word Associates Test (WAT) developed by Read (1993; 2004). The result revealed that students preferred indirect effective strategies to acquire new words, while indirect social cooperation was the least used strategy. However, students’ vocabulary strategy scores correlated negatively to the breadth and depth of students’ vocabulary knowledge. Students need special treatment to enhance their vocabulary knowledge.